The Idea of Determining a Socio-Culturally Sensitive Sheltering Framework for Seasonal Agricultural Workers - Hasgül, Esin; Özsoy, Fatma Ahsen (My University, 2019)
One of the most important factors driving major global changes is concept of “migration” among countries, between cities, even within the city, in various forms. Many people around the world work as “seasonal agricultural workers” in certain periods and have to migrate to a region other than the region where they live. The very strong social problematic issue that this situation constitutes is elementarily about sheltering. Different countries from world, especially the European countries face with this challenge in period of seasonal agriculture and countries try to find a solution according to their own sheltering policies. Since the situation occurs as a migration, people who migrate from their own homes to another region to generate an income can be defined also as migrants so that they need a temporary shelter to accommodate. Within this problematic, the scope of this research is to investigate the problems of the seasonal agricultural workers in worldwide and then more practically in Turkey and comprise a “Conceptual Framework” of socio-culturally sensitive sheltering solutions for them. The research acts like also a preliminary investigation of a “Research Project” that would be conducted in a specified rural area in Turkey. The methodology is based on documentation through achieve research and literature review; would be continued with observations on site and in-deep interviews. The outputs of the investigation would be used as inputs in the project and determine a subject-related scheme to open up detailed discussions on indeed related subjects.
Keywords: Seasonal Agriculture; Workers; Migration; Sheltering Problems; Temporary Shelters